COST AND PERSONNEL-EFFECTIVE TRANSFER USE OF SUGARCANE FIELD INTO ELEPHANT CASSAVA - Suwandi, '; Suhardjono, Hadi; Maroeto, '; Mindari, Wanti (PEDULI: Jurnal Ilmiah Pengabdian Pada Masyarakat, 2018)
ConvertingLandusecaneintocassavaelephantinKlintervillageaimedtohelpcostandlaboreffective.The declineofsoilhealth,sugarcaneyield,andfarmerincomes,encouragefarmerstoswitchbusinesses.Inorderto increasetheincomeoffarmers,theyshouldbeintroducedtoeasyandcheapalternativecultivations.Elephant cassavasareeasytomaintainandhavelow costinput,butstillareexcellentagriculturalproductsandmuch sought afterbyconsumers.Varietyprocessingofcassavaintofoodsandingredients,iscausingittobecome oneof customers favorites.Methods ofimplementation are through the tutorial,practice,monitoring andevaluation.By understanding the truecultivation techniques,itwillimprovethe levelofsoilfertility andproductivity.One alternativewas toadd organic matters tothe soil,which has been rarely practiced.Provision oforganic materials thathave asignificantimpactonsoilfertilityis indicatedby thecontentofhumate.Naturalhumateinsoilisin smallnumbers andneedhundreds ofyears tobe available.Application ofhumic acidin soilis expectedto dissolve,adsorbthemacroandmicroofsoilnutrients,thus increasingitsavailabilitytoplants.Monitoringand evaluation activities areconductedevery month,after the startofactivity andtroubleshootproblems thatoccur whentheactivitiestakeplace.